The effects of attitudes on sex roles, marriage, and homosexuality on premarital sex among never married Filipino youth - Fonacier, Maria Rosalyn Victoria Negre (Population Institute, College of Social Sciences and Philosophy, University of the Philippines, 2015)
This study has two major purposes: (1) to explore conservatism and develop a conservatism indicator and (2) to investigate the effects of conservatism on the premarital sex (PMS) behavior of the Filipino never married youth. The study used data from the Young Adult Fertility and Sexuality Study 4, which was carried out in 2013. It filtered its sample into the never married young adults who have never had PMS and those who had PMS in the 12 months prior to the survey. This selection resulted in a sample of 13,127 cases. Conservatism was measured using 14 statement items capturing five socio-cultural dimensions: 1) values on public display of affection, 2) attitudes on sexroles, 3) attitudes on marriage and cohabitation, 4) attitudes on divorce and remarriage, and 5) attitudes on homosexuality. A general conservatism indicator was created to measure the overall conservatism of the youth. Associations and effects of conservatism alongside other socio-demographic variables (age, socioeconomic status, urban exposure, religiosity, and educational attainment) on PMS behavior were tested using t-tests and regression analyses. All analyses were done by gender. The study results indicate that the Filipino unmarried youth are generally conservative. The lower the conservatism is, the higher the probability of engaging in PMS. Moreover, a gender difference exists in explaining conservatism and PMS behavior.